Effects of caffeine dose and administration method on time-trial performance: a systematic review and network meta-analysis - Xue, R.; Huang, J.; Chen, B.; Ding, L.; Guo, L.; Cao, Y.; Girard, O. (Nutrients, 2025)
Background/Objectives: Caffeine is a well-established ergogenic aid for endurance performance. However, the optimal intake strategy, specifically the administration method and dosage, remains uncertain. This systematic review and network meta-analysis compared the effectiveness of different caffeine administration methods and dosages on time-trial performance.